PENGARUH IMPLEMENTASI TRISILA TNI AL TERHADAP SEMANGAT PENGABDIAN PRAJURIT PANGKALAN TNI AL - Eko Arie Kurniawan; Sudardi (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
Trisila TNI AL is a guidance for every naval soldiers as codes of conduct to perform in their office and their environment. The implementation of this codes of conduct is required to keep and enhance the spirit and dedication of the "A" naval base's personnel in order to keep up with the new status as a main naval base. The aim of the journal is to analyze the influence of the Trisila TNI AL's implementation as firstorder and its influences on the soldiers' spirit and dedication as second order. This journal based on research to 75 respondents of the total population 297 soldiers in "A" naval base. This questionnaire in which is qualitative method mixed with the quantitative method that utilize the linear regression analysis. The result of this research shows that there are positive influences and significant effects of the implementation of trisila TNI AL, wheter as partial variables or simultaneous variables. r